Some Universal Constructions For I- Fuzzy Topological Spaces II (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Hamouda E. H. [J. of Advances in Math. Vol 6 (2014), 973-941] has introduced some universal constructions in the category FTOP, whose objects are the I-fuzzy topological spaces(x, ,F) where X is an ordinary set, is a fuzzy set in X and F is a family of fuzzy sets in X satisfying some axioms. In this paper we introduce the dual universal constructions, namely, fuzzy co-products, fuzzy co-equalizers and fuzzy pushouts for I-fuzzy topological spaces. Also we discuss some results concerning all such universal objects.